2014
DOI: 10.1210/jc.2013-3107
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism and Left Ventricular Mechanics: A Three-Dimensional Speckle Tracking Study

Abstract: SHT significantly affects LV deformation assessed by 2DE and 3DE speckle tracking. The improvement of LV mechanics after 1 year of levothyroxine treatment is significant but incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 27 publications
2
31
2
Order By: Relevance
“…In this study, the difference in EF of 3.4% was statistically significant. However, TDI analyses in other studies [13,22,23] showed disruption in LV systolic function in patients with ScH.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, the difference in EF of 3.4% was statistically significant. However, TDI analyses in other studies [13,22,23] showed disruption in LV systolic function in patients with ScH.…”
Section: Discussionmentioning
confidence: 77%
“…Identical as our results, Sunbul et al [15] found longitudinal myocardial dysfunction in 23 patients with ScH and their improvement after thyroid replacement therapy. Ilic et al [20] and Tadic et al [23] also showed a decrease of GLS in patients with ScH.…”
Section: Discussionmentioning
confidence: 94%
“…These results are also supported by a study that used 3D echocardiography. Indeed, Tadic et al showed that subclinical hypothyroidism affects LV deformation and that 1 year of levothyroxine treatment improved LV mechanics …”
Section: Discussionmentioning
confidence: 99%
“…This point is where TH appear to have a role in the physiopathology of DD, since low TH levels increase collagen synthesis and deposit in myocardium and decrease collagen metabolism in several ways [27][28][29][30] . Data from studies in non-renal patients with thyroid disorders have shown the relationship of low TH with decreased myocardial motility and increased collagen content [31,32] . In a cross-sectional study in patients with heart failure with preserved ejection fraction (>50%), T3 was found significantly reduced [33] .…”
Section: Discussionmentioning
confidence: 99%